Didaskalia jako „tekst w tekście" - Jerszowa, Sierafima (Acta Polono-Ruthenica, 2004)
A lexical-semantic analysis of the author’s text notes in A duck fowling, a play of A. Vampi lov’s marks out the following thematic groups (TG) that represent meaningful themes of the play and form the conceptual space of it: TG 1 - the vocabulary of „death” (funeral music, funeral procession); TG 2 - the vocabulary of „hunting” (duck fowling, rifle, etc.); TG 3 - the vocabulary of „social behaviour” („he hangs the wreath on the neck”, etc.); TG 4 - the vocabulary of „daily existence” (ordinary furniture, iron bed); TG 5 - the vocabulary of „atmospheric phenomena” (rain, a gleam of blue, etc.). The marked thematic groups of words, their kernel and peripheral components distinguish the conceptual space as an axis „life - game - death”